Pengaruh figur dosen terhadap implementasi program pengembangan diri mahasiswa, pengembangan minat dan bakat dan kebutuhan mahasiswa terhadap kemampuan penggunaan Internet dan Peningkatan Motivasi Belajar Mahasiswa pada Semester I Prodi PAI STAI Uluwiyah - Alif, Ikrom Abu (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
Lecturer is the figure of the architecture can shape the soul and character of students. Lecturers have the power to shape and build the student's personality to be a useful to religion, homeland and nation. The purpose of this study were: 1) Describe the effect of the implementation program Figured faculty self-development ability of students to use the internet. 2) Describe the effect of interest and talent development to the ability of internet usage. 3) Describe the effect of skill level and needs of the students of the ability of internet usage. 4) Describe the effect of the implementation program lecturers Figured personal development of students. 5) Describe the effect of interest and talent development towards Increasing student motivation to learn. 6) Describe the effect on the students' needs Increased motivation to learn. 7) Describe the effect of the implementation program lecturers Figured personal development of students, development interests and talents and the needs of students of the ability of internet usage. 8) Describe the effect of the implementation program lecturers Figured personal development of students, development interests and talents and the needs of students to Increasing student motivation to learn. From the analysis can be summarized as follows: 1) Figure lecturer for program implementation personal development of students, development interests and talents and the needs of students affect the ability of internet use in the first half Prodi PAI STAI Uluwiyah Mojosari (Fcount 90 237 (significance F = 0.000) . So Fhitung> Ftabel (90 237> 1.98) or Sig F <5% (0.000 <0.05) and PAI Prodi STIT Raden Wijaya Mojokerto. (Fcount 158 ​​057 (significance F = 0.000). So F count> F table ( 7158.057> 1.79) or Sig F <5% (0.000 <0.05). 2) Figure lecturer of the implementation of student self-development program, development interests and talents and the needs of students affect the students' Increased motivation in the first half Prodi PAI STAI Uluwiyah Mojosari (Fcount 41 096 (significance F = 0.000). So F count> F table (41 096> 1.98) or Sig F <5% (0.000 <0.05) and PAI Prodi STIT Raden Wijaya Mojokerto. (Fcount 65 758 (significance F = 0.000). So Fhitung> Ftabel (65 758> 1,79) or Sig F <5% (0.000 <0.05).